2019
DOI: 10.1080/00016357.2019.1645879
|View full text |Cite
|
Sign up to set email alerts
|

CBCT of Swedish children and adolescents at an oral and maxillofacial radiology department. A survey of requests and indications

Abstract: Objectives: This retrospective study investigated requests and indications for cone-beam computed tomography (CBCT) in children and adolescents over a 3-year period at one oral and maxillofacial radiology department. Specific aims were to determine what technical settings were used, which caregivers write the referrals, and how often and for what reasons re-exposure was necessary. Materials and methods: Patients <19 years of age who had been referred to the department and undergone a CBCT scan during 2015-2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 19 publications
1
21
0
2
Order By: Relevance
“…5,38 Currently, the management of canine impaction commonly includes acquiring diagnostic information obtained from CBCT, although little is known about how low-dose protocols could influence the choice of therapy or treatment outcome. 7,8,39 Further clinical studies are needed to identify how application of low-dose protocols can be selected and applied, using information from the current study on the visibility of the anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,38 Currently, the management of canine impaction commonly includes acquiring diagnostic information obtained from CBCT, although little is known about how low-dose protocols could influence the choice of therapy or treatment outcome. 7,8,39 Further clinical studies are needed to identify how application of low-dose protocols can be selected and applied, using information from the current study on the visibility of the anatomical structures.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The most common reason for obtaining a CBCT of the anterior maxillary region in adolescents is to assess impacted maxillary canines and their surrounding structures. 7,8 A missed diagnosis or delayed treatment results in 48% of patients developing root resorption of permanent adjacent incisors, which then leads to futher and often complicated orthodontic, surgical, and prosthetic treatments. [9][10][11] While the acquisition of three-dimensional (3D) CBCT volumes is rapidly increasing in popularity, the increased radiation-associated risks that CBCT entails warrant attention, especially regarding pediatric patients who have at least three times greater risk for developing cancer from radiation exposure than adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies in the literature investigating the use of CBCT in the pediatric population. 11,16,17,18,19 In this article, it is aimed to investigate the frequency of conic beam computed tomography among Turkish pedodontists, to evaluate its indications and to understand the need for training.…”
Section: Discussionmentioning
confidence: 99%
“…However, when they categorize children by age, it is stated that the second most common indication is cyst and tumour, especially in the 16-18 age group. 17 In some similar study on the pediatric patient group, CBCT has been used most frequently to evaluate tooth localization and tooth resorption. 11,16 In this study, it was reported that pedodontists most commonly used CBCT in cases of the cyst and/or tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Second and third highest scored were orthodontics (26.35%) and dental trauma (16.2%). In a Scandinavian study 9 , it was determined that the two most common reasons for a CBCT are assessment of an ectopic canine and localization of an impacted second premolar. A study published in year 2019 about digital radiography and CBCT 10 states that dental trauma was cited as the reason for using CBCT by 70 subjects (61.3%) subjects, dental development issues by 71% and pathology in the jaws by 75.8%.…”
Section: Indications For Radiographymentioning
confidence: 99%